2010
DOI: 10.3324/haematol.2009.020867
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant Pseudomonas aeruginosa infection in children undergoing chemotherapy and hematopoietic stem cell transplantation

Abstract: Pseudomonas aeruginosa is one leading gram-negative organism associated with nosocomial infections. Bacteremia is life-threatening in the immunocompromised host. Increasing frequency of multi-drug-resistant (MDRPA) strains is concerning. We started a retrospective survey in the pediatric hematology oncology Italian network. Between 2000 and 2008, 127 patients with Pseudomonas aeruginosa bacteremia were reported from 12 centers; 31.4% of isolates were MDRPA. Death within 30 days of a positive blood culture occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
74
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 24 publications
11
74
2
2
Order By: Relevance
“…Data on resistance rates in post-HSCT children are scarce [12,16,29]. Surpr resistance rates were mostly similar in children and in adults in our study.…”
Section: Outcomementioning
confidence: 67%
See 4 more Smart Citations
“…Data on resistance rates in post-HSCT children are scarce [12,16,29]. Surpr resistance rates were mostly similar in children and in adults in our study.…”
Section: Outcomementioning
confidence: 67%
“…Several studies reported risk factors for cephalosporin-resistant, ESBL-pro or MDR bacteria in cancer and HSCT patients [10,12,13,16,22,29,32]. Onl handful describe risk factors for carbapenem-resistant infections in popula involving but not limited to transplant patients, mainly for K. pneumoniae.…”
Section: Outcomementioning
confidence: 99%
See 3 more Smart Citations